PSIKOEDUKASI MENGENALI DAN MENGELOLA STRES MELALUI MEDIA POHON SYUKUR UNTUK MENINGKATKAN KESEHATAN MENTAL IBU-IBU DI DESA BUNGA KARANG - Astri, Putri Amanda; Dwi Hurriyati (Education, Language, and Arts: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to enhance the understanding and skills of mothers in Bunga Karang Village in managing stress through psychoeducation and the reflective Gratitude Tree activity. Initial observations showed that participants experienced emotional pressure due to multiple roles, household responsibilities, and economic demands. Through psychoeducation, participants gained new knowledge about the concept of stress, its causes, symptoms, and simple strategies to manage it. The Gratitude Tree activity helped participants shift their focus from daily stressors to positive life experiences while providing a safe and enjoyable medium for emotional expression. The activity also strengthened social support among participants through shared reflection. Manual measurement using the Perceived Stress Scale (PSS) indicated a decrease in stress scores from an average of 19.4 to 12.8, based on Cohen’s scoring guidelines. These findings demonstrate that community-based interventions combining psychoeducation and gratitude practices can effectively improve emotional regulation and mental well-being among mothers. Overall, the program is effective, easy to implement, and suitable for replication in similar community settings. Kegiatan pengabdian ini bertujuan meningkatkan pemahaman dan keterampilan ibu-ibu di Desa Bunga Karang dalam mengelola stres melalui psikoedukasi dan aktivitas reflektif Pohon Syukur. Observasi awal menunjukkan bahwa peserta mengalami tekanan emosional akibat peran ganda, tuntutan domestik, serta beban ekonomi keluarga. Melalui psikoedukasi, peserta memperoleh pemahaman mengenai konsep stres, faktor penyebab, tanda-tanda, dan strategi sederhana untuk mengelolanya. Aktivitas Pohon Syukur membantu peserta mengalihkan fokus dari tekanan menuju pengalaman positif, sekaligus menjadi sarana ekspresi emosional yang aman dan menyenangkan. Kegiatan ini juga memperkuat dukungan sosial antarpeserta melalui suasana kebersamaan. Pengukuran manual menggunakan Perceived Stress Scale (PSS) menunjukkan penurunan skor stres dari rata-rata 19,4 menjadi 12,8, berdasarkan pedoman penskoran Cohen. Temuan ini menunjukkan bahwa intervensi komunitas berbasis psikoedukasi dan latihan syukur mampu meningkatkan regulasi emosi dan kesehatan mental ibu-ibu. Secara keseluruhan, program ini efektif, mudah diterapkan, dan berpotensi direplikasi pada komunitas serupa.